Motivasi Kerja Sebagai Faktor Mediasi Diantara Gaya Kepemimpinan Melayani, Disiplin Kerja Dan Lingkungan Kerja Terhadap Performa Kerja Karyawan Generasi-Z Di Klinik X - Gozali, Darius Revin (Publikasi Indonesia, 2025)
This study was conducted to examine the mediating effect of motivation on the relationship between servant leadership style, work discipline, and work environment toward the performance of Generation Z employees. The research was carried out at Clinic X, involving 110 employees working at the clinic. Data were collected using a questionnaire consisting of 48 questions measured on a 7-point Likert scale, utilizing purposive sampling. The data were analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM).The majority of respondents in this study were male, comprising 58 percent of the total participants. The R² results indicated strong predictive accuracy for both motivation and employee performance, with values of 0.865 and 0.969, respectively. The variable with the largest effect size was motivation on employee performance (f² = 0.376), categorized as a large effect size. This was followed by work environment on motivation and employee performance (f² = 0.219 & 0.222), and discipline on motivation and employee performance (f² = 0.214 & 0.225), all categorized as medium effect sizes. The effect of servant leadership style on motivation and employee performance was categorized as small (f² = 0.109 & 0.131).Hypothesis testing results showed that all relationships were positive and significant, indicating that all ten proposed hypotheses were supported. In conclusion, discipline, work environment, and servant leadership style are significant factors influencing employee performance. It is recommended that future research employ more optimal data collection methods, broaden the research scope, and use a longitudinal research design,